Strategi Diversifikasi Atraksi Budaya Dalam Mendukung Pengembangan Wisata Desa Wakatobi - Muhadjir Suni; Muh. Zainuddin Badollahi (Universitas Muhammadiyah Gorontalo, 2020)
This study aims to determine and analyze the Diversification Strategy of Cultural Attractions in Support of Tourism Development in Wakatobi Village. This research method is qualitative research. The determination of the informants in this study was obtained by purposive sampling. The informants are community leaders and traditional leaders who are key informants. The results show that the opportunity for Wakatobi Regency to become a cultural tourism destination can be opened, because it is supported by the exoticism of local communities with their cultural diversity. The strategy that can be prioritized in the development of Wakatobi village tourism is the diversification of cultural attractions that are organized through institutions or Tourism Awareness Groups initiated by the community and funded by the local government and acting as an active facilitator. It seems that the political will and political commitment of leaders to maximize local government efforts need to be supported by tourism stakeholders from the government, private sector and the wider community, this is a weakness that needs to be covered so that the strategy in developing Community Base Tourism (CBT) tourism in Wakatobi provides a diversification of attractions. tour which is actually quite interesting to witness. Penelitian ini bertujuan untuk mengetahui dan menganalisa Strategi Diversifikasi Atraksi Budaya Dalam Mendukung Pengembangan Wisata Desa Wakatobi. Metode penelitian ini adalah penelitian kualitatif. Penentuan informan penelitian ini diperoleh secara Purposive sampling. Adapun informan yaitu tokoh masyarakat dan tokoh adat yang merupakan informan kunci. Hasil penelitian menunjukkan peluang kabupaten wakatobi menjadi destinasi wisata budaya dapat terbuka, karena didukung oleh eksotisme komunitas lokal dengan keberagaman budaya yang mereka miliki. Strategi yang dapat diprioritas dapat dalam pengembangan wisata desa Wakatobi adalah diversifikasi atraksi budaya yang terorganisasi melalui kelembagaan atau Kelompok Sadar Wisata yang diprakarsai masyarakat dan didanai oleh pemerintah daerah serta berperan sebagai fasilitator yang aktif. Tampaknya political will dan political comitment pemimpin untuk memaksimalkan upaya pemerintah daerah perlu di dukung oleh stekholder pariwisata dari pihak jajaran pemerintah, swasta dan masyarakat luas hal merupakan kelemahan yang perlu ditutupi agar strategi dalam pengembangan wisata Community Base Tourism (CBT) di Wakatobi menyajikan adanya diversifikasi atraksi wisata yang sesungguhnya cukup menarik untuk disaksikan.